The Economics of Bounded Rationality, Entrepreneurship and Institutional Evolution - Richard H. Day (The Research Institute of Industrial Economics (IUI), 1989)
Bounded rationality provides a fundamental economic explanation for non-rational modes of behavior. These non-rational modes underlie both the erratic perturbations of entrepreneurship and the systematic waves of diffusion they initiate which in turn guarantee that the economy operates out of equilibrium. Continuing adjustments out of equilibrium are made possible by financial intermediation. They imply asymmetric changes in individual welfare. The markets for entrepreneurship, ownership and control that liberate creativity and boundedly rational decision-making, therefore, also lead inevitably to conflict among various social groups. Democratic mechanisms for correlating public and private interest that enlist the voluntary participation of agents who are sometimes made worse off in the continuing process of social transformation and which restore access to markets for those who lose is therefore an essential part of a modern economic system. The dialectical interaction among market al1ocations, non-market buffering and stabilizing institutions and democratic process is thus fundamental. Reforms that are based on this interaction achieve voluntary self-transformations. Those that do not, ultimately fall victim to involuntary forces.
Keywords: D81; L22; L26; 330; Entrepreneurship; bounded rationality; institutional evolution